Irrigation Water Productivity and Operation, Sustainability and Climate Change - Ricart, Sandra; Rico, Antonio M.; Olcina, Jorge (IntechOpen, 2019)
The management of irrigation systems is context-dependent, socially constructed, and technically uncertain. An example of complex social-ecological systems, irrigation deals with both the ecosystem uncertainty and the implementation of new technological systems and water management options. Issues to be addressed by irrigation systems at the global scale include: water productivity and food security, field operation and maintenance, spate irrigation in climate change scenarios, and vulnerability of environmental resources. This book provides examples of some of the current challenges faced by irrigation systems from technical and social perspectives. The book offers an easy-to-follow format focused on different case studies combining evidence-based solutions for increasing resilience and reducing vulnerability of irrigation systems in semi-arid and arid regions across the world.